COGNITIVE SPHERES OF ICONOTROPISM - Vasylkiv, H. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
In contemporary literary research, wecan see a tendency for avoiding the term ’iconotropism’ or vague interpretation and awareness of its role in fiction. Therefore, in this article, we considerit expedient to follow in detail the definition of the term, its etymology, and evolution, as well as, in the long run, its integration in to the literary field and signs in postmodern literature, which is the purpose of this study. It is important to note that in the article we will rely on the semantic-cognitive analysis of iconotropism, as the meaning of this term, in our opinion, is fully displayed namely in the awareness of the mental and biological processes of the human body, and its evolution. Recently, there has been an increasing interest in the examination of literary studies’ questions with cognitivism. "Cognitive literary studies", whicharoseat the end of the 20th century, still remain on the margin of literature research. However, nonetheless, in our opinion, it is worth paying attention precisely in the context of the study of iconotropism. The methodological basis of the article is the works of literature researchers Ellen Spolsky, Roston Murray, and neuroanthropologist Terrence Deacon, who avouchthe expedience of studying literature precisely through the prism of the cognitive processes of the individual. The nature of iconotropism is directly connected with the evolution of man and his natural craving for icons. As a result, several interpretations of "iconotropism" have been identified; its development has been traced in a diachronic aspect; the cognitive spheres of iconotropism have been out lined; it has been proven that this very term quite well denotes what is an actual basis of a literary work – the visual interpretation of its content, the peculiarity of the reader’s perception of a literary piece, and, finally, people’s passion for art (in this consists practical value and novelty of this study). Analyzing the poetics of postmodernism in the context of iconotropy, the peculiarity of such iconic concepts as "labyrinth", "rhizome", "fractal" has been characterized.